Size distribution of magnetite nanoparticles in a polymer matrix - Ali-zade, R.A.; Ramazanov, M.A.; Sadykhov, R.Z. (Functional Materials, 2009)
The magnetite nanoparticle size has been studied as a function of the concentration thereof in polymer matrix. The magnetite nanoparticle size distribution has been determined. The magnetite nanoparticle magnetization has been calculated taking into account the magnetic dipole-dipole interaction. Досліджено розміри наночастинои магнетиту залежно від їх ионцентрації у полімерній матриці. Визначено розподіл наночастинои магнетиту за розмірами. Обчислено намагнічення наночастинои магнетиту з урахуванням магнітної диполь-дипольної взаємодії. Исследован размер наночастиц магнетита в зависимости от их концентрации в полимерной матрице. Определено распределение наночастиц магнетита по размерам. Вычислено намагничивание наночастиц магнетита с учетом магнитного диполь-дипольного взаимодействия.